Optimum Detection Location-Based Cooperative Spectrum Sensing in Cognitive Radio - Zhang, Hongtao; Wang, Xiaoxiang; Kuo, Geng-Sheng; Bohnert, Thomas Michael (Společnost pro radioelektronické inženýrství, 2010)
Cognitive radio arises as a hot research issue in wireless communications recently, attributed to its capability of enhancing spectral efficiency and catering for the growing demand for bandwidth. As a good embodiment of cognitive radio’s unique feature, i.e. making use of every bit spectral resource, spectrum sensing plays a vital role in the implementation of cognitive radio. To alleviate negative effect on cooperative spectrum sensing brought by bit errors, we introduce a novel concept, i.e. Optimum Detection Location (ODL) and present two algorithms of different computational complexity for locating ODL, together with an ODL-Based cooperative spectrum sensing scheme, with the motivation to exploit the gain derived from geographic advantages and multiuser diversity. Numerical and simulation results both demonstrate that our proposed spectrum sensing scheme can significantly improve the sensing performance in the case of reporting channel with bit errors.
Keywords: Cognitive radio; spectrum sensing; Wireless Region Area Network (WRAN); Optimum Detection Location (ODL)